Assessment of Nursing Care and Teaching: A Qualitative Approach - Jose Manuel Martínez-Linares (International Journal of Environmental Research and Public Health, 2019)
Background: The reform of the Spanish higher education to adapt to the European Higher Education Area involves, among other issues, the students’ participation in the curriculum assessment. The aim is to understand the insights of both nursing professionals and current undergraduate students of nursing on the connection between the knowledge acquired throughout the degree and the professional healthcare practice. Methods: An exploratory, descriptive qualitative study was carried out at a Spanish University. By convenience sampling, twelve nursing professionals and twelve 4th-year students of the Degree in Nursing were included. In two phases, twelve semi-structured interviews and two focus groups were conducted in order to triangulate data. A thematic analysis of data was carried out, later to be coded by two researchers. Results: Two main themes were identified: Evidence-based nursing vs. experience-based nursing, and a theory-practice gap. The topics that were specifically highlighted were the coexistence between professionals who work according to evidence and those whose work is based on experience, and the lack of connection between the training received during the degree and actual healthcare practice. Conclusion: Nursing care work varies in terms of the implementation of evidence-based care. Nursing training is perceived as being affected by a theory-practice gap. To achieve the linking between nursing theory and practice, a great effort on stakeholders would be needed.